2015
DOI: 10.1111/jora.12220
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Socio‐Motivational Relationships With Teachers, Amygdala Response to Teacher's Negative Facial Expressions, and Test Anxiety

Abstract: The amygdala is essential for processing emotions, including the processing of aversive faces. The aim of this multimethodological study was to relate the amygdala reactivity of students (N = 88) toward teachers' fearful and angry faces, to students' relationship with their teachers. Furthermore, students' neural responses during the perception of teachers' faces were tested as predictors of test anxiety (controlling for neuroticism as a potential trait anxiety effect). Multiple regression analysis revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 157 publications
(140 reference statements)
0
3
0
3
Order By: Relevance
“…As a situation-specific trait, dispositional workplace anxiety is aligned with other situation-specific anxieties, such as test anxiety (Spielberger, Anton, & Bedell, 1976) and competitive sports anxiety (Martens et al, 1990). Empirical evidence substantiates this distinction, with findings revealing low to moderate relationships between situation-specific anxieties (e.g., test anxiety, sport anxiety) and general trait anxiety (Cerin, 2004;Mandler & Sarason, 1952;Raufelder et al, 2016).…”
Section: Dispositional and Situational Workplace Anxietymentioning
confidence: 96%
“…As a situation-specific trait, dispositional workplace anxiety is aligned with other situation-specific anxieties, such as test anxiety (Spielberger, Anton, & Bedell, 1976) and competitive sports anxiety (Martens et al, 1990). Empirical evidence substantiates this distinction, with findings revealing low to moderate relationships between situation-specific anxieties (e.g., test anxiety, sport anxiety) and general trait anxiety (Cerin, 2004;Mandler & Sarason, 1952;Raufelder et al, 2016).…”
Section: Dispositional and Situational Workplace Anxietymentioning
confidence: 96%
“…In line with this, Raufelder et al. () observed that the better adolescent students reported the quality of their relationship with teachers to be, the higher their amygdala response to fearful teacher‐faces and the higher their worry levels in test situations, making these students especially susceptible to reduced academic performance (McDonald, ). Lower performance may, in turn, negatively affect subsequent ASC (Marsh et al., ).…”
Section: Discussionmentioning
confidence: 85%
“…Les individus très angoissés sont plus susceptibles que les individus peu angoissés d'adopter des modes de réflexion et des comportements inadéquats pour la tâche à accomplir, ce qui diminue leur performance (Sarason, Sarason et Pierce, 1990 ;Spielberger, 2013). Les élèves très angoissés ont souvent le sentiment qu'ils n'ont pas de prise sur les résultats des évaluations (Schunk, 1991 (Raufelder et al, 2016).…”
Section: Conséquences De L'anxiété Liée Au Travail Scolaireunclassified
“…Cette relation est plus marquée chez les filles que chez les garçons, ce qui peut laisser penser que les parents éprouvent plus de difficultés à communiquer avec leurs fils et à lutter contre ce qui les met mal à l'aise. Ce constat corrobore les conclusions de recherches antérieures, qui montrent que les garçons ont tendance à considérer toute intervention de leurs parents comme une forme de pression, alors que les filles parviennent mieux à différencier le soutien de la pression de leurs parents (Leff et Hoyle, 1995 ;Raufelder et al, 2016).…”
Section: Conséquences De L'anxiété Liée Au Travail Scolaireunclassified